Preoperative Level of Insulin-Like Growth Factor Binding Protein 2 Predicts The Suboptimal Outcome After Primary Debulking Surgery in Patients with Advance Ovarian Cancer - Pande Kadek Aditya Prayudi; I Gde Sastra Winata; I Nyoman Gede Budiana; Kade Yudi Saspriyana; I Nyoman Bayu Mahendra; Ketut Suwiyoga (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: The need for clinically useful biomarkers which can predict the surgical outcome after primary debulking surgery (PDS) in patients with advance ovarian cancer (AOC) is really important. Insulin-like growth factor-binding protein 2 (IGFBP2) is the main binding protein expressed by ovarian cancer cells, which plays a prominent role in promoting proliferation, driving invasion, and suppressing apoptosis. This study was conducted to assess the performance of IGFBP2 in predicting the surgical outcome after PDS in patients with AOC.METHODS: Twenty-four subjects with AOC (Stage IIIc/IV) who underwent PDS were recruited consecutively. Clinicopathologic data were obtained from subjects' medical records. Blood samples were withdrawn form each subject and preoperative level of IGFBP2 were measured using enzyme-linked immunosorbent assay (ELISA). Multivariate analysis was employed to test the performance of multiple predictors of surgical outcome.RESULTS: Eighteen patients (75%) had suboptimal outcome after PDS. Mean IGFBP2 level was significantly higher in the suboptimal group (1157.5±359.9 ng/mL vs. 679.1±504.5 ng/mL, p=0.018). In bivariate model, higher preoperative level of IGFBP2 predict the suboptimal outcome with good accuracy (AUC: 0.796, sensitivity: 83.3%, specificity: 83.3%, p=0.033, optimal threshold level 870 ng/mL). Higher IGFBP2 level was associated with higher risk of suboptimal outcome, although IGFBP2 was not an independent risk factor (adjusted OR: 5.0, 95% CI: 0.43-57.9, p=0.198).CONCLUSION: IGFBP2 is a novel and promising biomarker for surgical outcome prediction following PDS in AOC patients. Since it is predictive for suboptimal outcome, patients with higher preoperative level of IGFBP2 needs more thorough preoperative evaluation as well as meticulous surgical technique to optimize the surgical outcome.KEYWORDS: IGFBP2, advance ovarian cancer, PDS, surgical outcome, predictor